MASS REARING OF SITOTROGA CEREALELLA (OLIVIER) (LEPIDOPTERA: GELECHIIDAE) IN NEWLY DESIGNED CHAMBERS - Hamed, M.; Nadeem, S. (The Nucleus, 2010)
Mass rearing of Sitotroga cerealella (Olivier) (Lepidoptera: Gelechiidae) a factitious host of Trichogramma chilonis (Hymenoptera: Trichogrammatidae) commonly used in the laboratory was compared with small scale rearing in glass jars. In mass rearing of host, S. cerealella eggs measuring 0.4, 2.5, 3.3, 4.1 and 5.0 g after seeding on 3, 4, 5 and 6 kg of wheat grains on three trays inside each tin chamber gave 43.7, 52.4, 59.6 and 77.9 g of eggs, enough to prepare 991, 1179, 1326 and 1756 number of Trichogramma cards, respectively as compared to small scale rearing by the use of glass jars, where 3.7 g of eggs were obtained to produce 84.4 cards of Trichogramma. Mass rearing in tin chambers, where 6 kg grains were used, gave 21% more eggs production than glass jars to get enhanced production of the reared insects.